ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PERUSAHAAN TRANSPORTASI JASA PT SRIWIJAYA AIR - Maria Helena Fatima Da Cruz Oliveira; Giri Kusnanta (Journal of Tourism and Economic, 2018)
This study aims to determine the effect of service quality in the form of reliability, responsiveness, assurance, empathy and tangibles to customer satisfaction in PT.Sriwijaya Air airline. The research data was collected from 100 respondents. The respondents of this research are Timor Leste students who are studying in Yogyakarta and have used PT. Sriwijaya Air. Using Pruposive Sampling method technique with certain consideration and giving questionnaires to every individual encountered with certain criteria. The data collection tools are questionnaires in the form of Likert Scale while the analytical tools of description and Multiple Linear Regression. Data processing is helped of SPSS program. The analysis results show (1) Quality of service which include reliability, responsiveness, assurance, empathy and tangibles simultaneously have a positive and significant effect on customer satisfaction at Sriwijaya Air . Partially there are only four variables that have a positive and significant effect on customer satisfaction are responsiveness (0.262), assurance (0.310), empathy (0.320) and physical evidence (0.757), while one other variable is reliability has no positive and significant effect -0.058) to customer satisfaction. (2) The research results show that 94% of the satisfaction of Sriwijaya Air airline customers is influenced by the quality of service consisting of reliability, responsiveness, assurance, empathy and physical evidence. The remaining 6% is the influence of other variables that are not examined such as price, cost, product quality and emotional.Keywords: service quality, customer satisfaction, sriwijaya airline.